Keragaman Fenotipik dan Kekerabatan Plasma Nutfah Talas (Colocasia esculenta) Pulau Bangka berdasarkan Karakter Morfologi - Kusumawati, Yani; Mustikarini, Eries Dyah; Prayoga, Gigih Ibnu Prayoga (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Germplasm diversity of local taro in Bangka as genetic resources for plant breeding purposes is still unknown. This research aimed to provide information on Bangka Taro’s variability and relationship for plant breeding programs. This research was conducted in December 2017 until February 2018. Characterization of the germplasm was performed on qualitative and quantitative parameters. Analysis of morphological relationships used the UPGMA method. Exploration obtained 27 germplasm of Bangka local taro. The results of the morphological relationship analysis showed nine clusters at a 0.57 coefficient (57%). Cluster one consisted of Tungkuk, Sayur, Hitam/Nyatoh, Rakit Hijau, Lilin, and Cantik Manis accessions. Cluster two consisted of Rakit Hitam accession. Cluster three consisted of Ganjung, Trans 2, Sungai Tebuk and Trans 1 accessions. Cluster four consisted of Sayang Anak, Pak Ugo and Trans 3 accessions. Cluster five consisted of Angit and Kelat Mentak Kelapa accessions. Cluster six consisted of Pelawan Toboali, Wangi/Colet and Simbang accessions. Cluster seven consisted of Alar accession. Cluster eight consisted of Pelawan Rukem, Kelat Mentak Rukem, Selaseh, Pinangbo and Telok Simbang accessions.Cluster nine consisted of Butir/Pikul and Butir Mentaram accessions. Bangka local taro had wide phenotypic variability in the observed morphological characters. Keywords: accesion, fenotipic, cluster, relationship, variability